Fukahâ metodunun genel yapısı üzerine - Yığın, Adem (Marmara Üniversitesi İlahiyat Fakültesi Dergisi, 2003)
Over The General Character of The Jurists Method The discipline of Usul al-Fiqh is a branch of knowledge which is peculiar to Muslim society and Islamic law. Yet it is impossible to say that this discipline, which is a prerequisite for the students of Islamic law, has received the attention it deserves. It can be said that the most important way of exploring the basic structure and evolution process of a discipline is to analyze the literature produced by those who specialize on that discipline. Literature of Usul al-Fiqh is analyzed in relevant works by dividing into three categories from the perspective of the methods used in it: those who follow the method of jurists, those who follow the method of theologians and those who combine both methods. The goal of this article is to analyze the method of the jurists. The article looks at the perspectives on the method of jurists in the relevant literature and explores the characteristics of the method of jurists by looking at the work of such jurists as Jassas (d. 370/980), Dabusi (d. 430/1038), Bazdawi (d. 482/1089) and Sarakhsi (d. 483/1090). In conclusion, the general character of the jurists method is presented. At the same time, the conventional views on the method of jurists in the existing literature are tested and evaluated with a critical approach.